PERUBAHAN PERSEPSI ANGGOTA DPRD DAERAH ISTIMEWA YOGYAKARTA TERKAIT MATERIALITAS PADA PEMBERIAN OPINI OLEH BPK RI - Yestias Maharani (Optimum: Jurnal Ekonomi dan Pembangunan, 2017)
The objective of this research is to assess perceptions of financial statement users toward current opinion issued by Supreme Audit Board (Badan Pemeriksa Keuangan/BPK) and compare how perception of financial statement users toward modified opinion which was created by adding additional information related to materiality, adding a rule in accounting standard to disclose materiality level, involving financial statement users in setting materiality level, and conducting knowledge transfer to financial statement users. This research employed survey methodology using questionnaires. Respondents of the survey were local legislators in Special Region of Yogyakarta (Daerah Istimewa Yogyakarta/DIY). There were 32 questionnaires answered. Data collected from 32 questionnaires were tested using descriptive statistic, validity test, reliability test and Wilcoxon Signed Rank Test. The result showed that financial statements users do not really understand materiality aspect in the issuance of opinion BPK. After they received additional information related to materiality, they acknowledged that they had better understand of information stated in financial statements audited by BPK. In addition, financial statements users thought that they need to be involved in setting materiality levels. They also thought that they need knowledge transfer through training or workshop to improve their understanding of information stated in financial statements audited by BPK.